2006
DOI: 10.1038/sj.npp.1301234
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Neurons Immunoreactive for Calcium Binding Proteins are Reduced in the Prefrontal Cortex in Major Depression

Abstract: Post-mortem morphometric studies report reductions in the average density and size of cortical neurons in the dorsolateral prefrontal cortex (dlPFC) and orbitofrontal cortex (ORB) in major depressive disorder (MDD). The contribution of specific neuronal phenotypes to this general pathology in depression is still unclear. Post-mortem sections from the dlPFC and ORB regions of 14 subjects with MDD and 11 controls were immunostained to visualize calbindin-immunoreactive (CB-IR) and parvalbumin-immunoreactive (PV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
241
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(269 citation statements)
references
References 97 publications
(134 reference statements)
20
241
2
6
Order By: Relevance
“…Interneuron-related disorders may arise when cortical development goes awry (Levitt et al, 2004;Di Cristo, 2007). An aberrant number and/or distribution of specific subsets of cortical interneurons have been linked to several major neurological disorders, including epilepsy (Powell et al, 2003;Garbelli et al, 2006), schizophrenia (Reynolds et al, 2002;Lewis et al, 2005;Daskalakis et al, 2007), and depression (Rajkowska et al, 2007). In a rat model of fetal alcohol syndrome, one outcome of ethanol exposure during the first postnatal week is an increase in the number of cortical calretinin-IR neurons in the adult (Granato, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interneuron-related disorders may arise when cortical development goes awry (Levitt et al, 2004;Di Cristo, 2007). An aberrant number and/or distribution of specific subsets of cortical interneurons have been linked to several major neurological disorders, including epilepsy (Powell et al, 2003;Garbelli et al, 2006), schizophrenia (Reynolds et al, 2002;Lewis et al, 2005;Daskalakis et al, 2007), and depression (Rajkowska et al, 2007). In a rat model of fetal alcohol syndrome, one outcome of ethanol exposure during the first postnatal week is an increase in the number of cortical calretinin-IR neurons in the adult (Granato, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of cortical interneuron morphology and neurochemistry presents a complex, incompletely understood picture of neural development (Wonders and Anderson, 2006). Moreover, cortical interneuron dysfunction has been implicated in several neurological disorders with developmental origins (Levitt et al, 2004;Di Cristo, 2007), including epilepsy (Powell et al, 2003;Garbelli et al, 2006), schizophrenia (Reynolds et al, 2002;Lewis et al, 2005;Daskalakis et al, 2007), and depression (Rajkowska et al, 2007). The current study examined a subpopulation of rat cortical interneurons that produced tyrosine hydroxylase (TH), the first, rate-limiting catecholaminergic enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…29 In addition, imaging studies have identified reductions in occipital cortex g-aminobutyric acid (GABA) levels in patients with MDD. 30,31 We hypothesize that patients with END may have a greater imbalance in concentrations of GABA than those with ERD, resulting in a poor response to SSRI antidepressants. There were no differences between either of the patient groups and the control subjects in ALFF of the lingual gyrus, in the present study, but there was a difference between patients with ERD and those with END.…”
Section: Discussionmentioning
confidence: 99%
“…Existen estudios que reportan un incremento del GABA en la corteza occipital después de un tratamiento antidepresivo efectivo con terapia electroconvulsiva 53 , y estudios que reportan concentraciones GABAérgicas normales en pacientes deprimidos recuperados y sin medicación 54 . El estudio de la depresión, como hemos mencionado con anterioridad, implica una correlación multidisciplinaria para poder desentrañar la compleja gama de causas que la integran, por lo que en un intento de continuar dilucidando la relación del GABA con la depresión se han realizado estudios post mortem que reportan una reducción en el tamaño y la densidad de las neuronas en la corteza prefrontal dorsolateral en pacientes con depresión mayor, relacionándolo con la reducción de las concentraciones corticales de GABA 55 .…”
Section: Estudios De Espectroscopía En Pacientes Con Depresiónunclassified